Efforts of the human immune system to maintain the peripheral CD8+ T cell compartment after childhood thymectomy. Issue 1 (December 2016) - Zlamy, Manuela; Almanzar, Giovanni; Parson, Walther; Schmidt, Christian; Leierer, Johannes; Weinberger, Birgit; Jeller, Verena; Unsinn, Karin; Eyrich, Matthias; Würzner, Reinhard; Prelog, Martina
Abstract Background Homeostatic mechanisms to maintain the T cell compartment diversity indicate an ongoing process of thymic activity and peripheral T cell renewal during human life. These processes are expected to be accelerated after childhood thymectomy and by the influence of cytomegalovirus (CMV) inducing a prematurely aged immune system. The study aimed to investigate proportional changes and replicative history of CD8+ T cells, of recent thymic emigrants (RTEs) and CD103+ T cells (mostly gut-experienced) and the role of Interleukin-(IL)-7 and IL-7 receptor (CD127)-expressing T cells in thymectomized patients compared to young and old healthy controls. Results Decreased proportions of naive and CD31 + CD8+ T cells were demonstrated after thymectomy, with higher proliferative activity of CD127-expressing T cells and significantly shorter relative telomere lengths (RTLs) and lower T cell receptor excision circles (TRECs). Increased circulating CD103+ T cells and a skewed T cell receptor (TCR) repertoire were found after thymectomy similar to elderly persons. Naive T cells were influenced by age at thymectomy and further decreased by CMV. Conclusions After childhood thymectomy, the immune system demonstrated constant efforts of the peripheral CD8+ T cell compartment to maintain homeostasis. Supposedly it tries to fill the void of RTEs by peripheral T cell proliferation, by at least partly IL-7-mediated mechanisms and by proportional increase of circulating CD103+ T cells, reminiscent of immune aging in elderly. Although other findings were less significant compared to healthy elderly, early thymectomy demonstrated immunological alterations of CD8+ T cells which mimic features of premature immunosenescence in humans.